Plasma rico em plaquetas: padronização em equídeos, criopreservação e efeito terapêutico na desmite do ligamento supraespinhoso de equinos - Priscila Fantini (2014)
The therapeutic potential, its low cost and easiness of preparation, Platelet Rich Plasma (PRP) use in regenerative medicine has been unveiled by many studies. However, many gaps remain to be clarified regarding its therapeutic use. This study objectived to: (1) standardize a protocol to obtain equine PRP, using a single centrifugation step in order to recover a majority of the platelets and a minimal amount of leucocytes; (2) validate a closed commercial system for equine PRP obtainment; (3) define a cryopreservation system for equine PRP after slow refrigeration; (4) evaluate the therapeutic effects of PRP on desmopathy of the supraspinous ligament of equines. Protocols using low-speed simple centrifugation were most efficient concentrating platelets, recovering reduced amounts of leucocytes and presented with acceptable levels of TGF-1. Cryopreservation of equine PRP using 3% DMSO, slowly refrigerated to 4-5ºC at a controlled rate of -0,07ºC/minute, followed by freezing at liquid nitrogen (-196ºC), presented a lower percentage of platelet activation when evaluated by optic microscopy, maintaining approximately 35% of the initial value of platelet aggregation. This study suggest the use of PRP for treating desmopathy of the supraspinous ligament of equines, given no adverse effect was observed, accelerating by 5.85 times the resolution time of lesions, reducing the area of the induced lesion, when evaluated by ultrasound. Results presented here support to further studies on the therapeutic application of PRP.